Contribution of diet to lead exposure among children aged 1 to 7 years in La Plata, Buenos Aires - Martins, Enrique Francisco (2018)
Introduction. Lead is a toxic metal which, even at low blood levels, can alter normal neurodevelopment in children, so no blood lead level is acceptable. Lead absorption from diet accounts for the highest contribution to blood lead levels in the population who is not exposed to contaminated environments or because of their occupation. The objective of this study was to determine the contribution of diet to lead exposure among children aged 1 to 7 years who attended Hospital de Niños de La Plata for health check-ups. Population and methods. The study was conducted between June 2015 and May 2016. A questionnaire on the frequency of food intake was administered to 91 children whose average age ± standard deviation was 3.0 ± 1.7 years, and foods included in the analysis were selectedbased on this questionnaire. Selected foods were purchased from different regional stores. Composite samples were made up of different food groups. Lead levels corresponding to each food group were determined and, finally, the daily intake of lead was estimated for the studied population. Results. The daily intake of lead was 138 µg/day. The food groups with the higher intake rates were processed meat products (15.4%), bakery products (14.8%), milk (12.5%), and meat (11.7%). Conclusions. Children aged 1 to 7 years attending a public hospital in La Plata have a lead burden from dietary intake of 138 µg/day.